ANALISIS KARAKTER UTAMA DALAM FILM THE GREAT GATSBY (2013) - Jihad Dzikri Fauzi; Mia Rahmawati Yuwita (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
Movies are identical to characters. If the characters are less attractive, the audience's interest can also decrease. Therefore, it is also important that a character has characteristics that specifically describe the character's personality and what traits are contained in him. For instance, The Great Gatsby (2013) movie features the main character with a romantic theme taken during the era of World War I. Gatsby's interesting character will make people interested in watching the film. The purposes of this study are to find out the characteristics of Gatsby and the six pillars of character attached to Gatsby. The method used in this analysis is qualitative. The data used in this study is a conversation, taken from a transcription, from a film entitled The Great Gatsby (2013), which can be watched streaming on the HBO application. The object of the research is the main character, namely Gatsby. This study shows that Gatsby has arrogant characteristics, feels nervous about something, feels loved, is persistent, and has high expectations. And according to the Josephson Of Institute's six pillars, there are several categories of six pillars within Gatsby, namely caring, respect, responsibility, and citizenship. Keywords: Six Pillars of Character, Character, The Great Gatsby